Species diversity of non-tuberculous mycobacteria isolated from humans, livestock and wildlife in the Serengeti ecosystem, Tanzania - Katale, Bugwesa Z (BMC Infect Dis, 2014)
BACKGROUND: Non-tuberculous mycobacteria (NTM), which are ubiquitous micro-organisms occurring in humans, animals and the environment, sometimes receive public health and veterinary attention as opportunistic disease-causing agents. In Tanzania, there is limited information regarding the diversity of NTM species, particularly at the human-livestock-wildlife interface such as the Serengeti ecosystem, where potential for cross species infection or transmission may exist. METHODS: Mycobacterial DNA was extracted from cultured isolates obtained from sputum samples of 472 suspect TB patients and 606 tissues from wildlife species and indigenous cattle. Multiplex PCR was used to differentiate NTM from Mycobacterium tuberculosis complex (MTBC) members. NTM were further identified to species level by nucleotide sequencing of the 16S rRNA gene. RESULTS: A total of fifty five (55) NTM isolates representing 16 mycobacterial species and 5 isolates belonging to the MTBC were detected. Overall, Mycobacterium intracellulare which was isolated from human, cattle and wildlife, was the most frequently isolated species (20 isolates, 36.4%) followed by M. lentiflavum (11 isolates, 20%), M. fortuitum (4 isolates, 7.3%) and M. chelonae-abscessus group (3 isolates, 5.5%). In terms of hosts, 36 isolates were from cattle and 12 from humans, the balance being found in various wildlife species. CONCLUSION: This study reveals a diversity of NTM species in the Serengeti ecosystem, some of which have potential for causing disease in animals and humans. The isolation of NTM from tuberculosis-like lesions in the absence of MTBC calls for further research to elucidate their actual role in causing disease. We are also suggesting a one health approach in identifying risk factors for and possible transmission mechanisms of the NTM in the agro-pastoral communities in the Serengeti ecosystem. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-014-0616-y) contains supplementary material, which is available to authorized users.